A New Look at Shorter Hours of Work in the CEP - White, Julie (Just Labour: A Canadian Journal of Work and Society, 2002)
This paper argues that we need to look again at hours of work. One out of every five Canadians is working more than 40 hours a week as their regular hours, while one out of ten work over 50 hours. On top of this, overtime is excessive - paid overtime alone is the equivalent of 225,000 full-time jobs. A major study by the CEP in the pulp and paper industry has shown that overtime may be more expensive than hiring additional workers and that workers are willing to reduce overtime in order to save or create jobs. On reducing regular hours of work, the CEP has found that additional days away from work, once negotiated and experienced, are extremely popular. While more time off is about job creation, better health and safety and improving family and social life, it opposes the lean and mean approach of business corporations.